2001
DOI: 10.1086/320955
|View full text |Cite
|
Sign up to set email alerts
|

Why Is the Fraction of Four‐Image Radio Lens Systems So High?

Abstract: We investigate the frequency of two-and four-image gravitational lens systems in the Jodrell-VLA Astrometric Survey (JVAS) and Cosmic Lens All-Sky Survey (CLASS), and the possible implications for dark matter halo properties. A simple lensing statistics model, which describes lens galaxies as singular isothermal ellipsoids with a projected axis ratio distribution derived from the surface brightness ellipticities of early-type galaxies in the Coma cluster, is ruled out at the 98% level since it predicts too few… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
124
0

Year Published

2002
2002
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(133 citation statements)
references
References 68 publications
9
124
0
Order By: Relevance
“…The inclusion of nonsphericity in the lenses is beyond the scope of this paper. Although previous studies found that the introduction of ellipticities d0.2 into nearly singular profiles has little effect on the lensing cross section and image magnification, the strong magnification bias will favor a high fraction of four-image lenses (Rusin & Tegmark 2001), as well as an increase in the number of multiple image systems. One consequence of this effect will be to double the expected microlensing rate (see x 6).…”
Section: Lens Populationmentioning
confidence: 82%
“…The inclusion of nonsphericity in the lenses is beyond the scope of this paper. Although previous studies found that the introduction of ellipticities d0.2 into nearly singular profiles has little effect on the lensing cross section and image magnification, the strong magnification bias will favor a high fraction of four-image lenses (Rusin & Tegmark 2001), as well as an increase in the number of multiple image systems. One consequence of this effect will be to double the expected microlensing rate (see x 6).…”
Section: Lens Populationmentioning
confidence: 82%
“…5 The data give the shape of the light distribution, while what we need is the shape of the mass distribution. The mass and light shapes may not be correlated on a case-by-case basis, but for our purposes it is sufficient to assume that their distributions are similar (see Rusin & Tegmark 2001). 6 It is possible to obtain an analytic NFW model by putting the elliptical symmetry in the potential rather than the density (e.g., Golse & Kneib 2002;Meneghetti et al 2003).…”
Section: Definitionsmentioning
confidence: 99%
“…However, symmetric models only produce two-image lenses and cannot be used to interpret the statistics of each morphology separately. More recently, numerical studies have been performed with more realistic elliptical lens models (e.g., King & Browne 1996;Wallington & Narayan 1993;Kochanek 1996;Keeton, Kochanek, & Seljak 1997;Rusin & Tegmark 2001). While numerical calculations are certainly valuable, they tend to obscure the roles of competing contributions to what is being calculated.…”
Section: Introductionmentioning
confidence: 99%